Expertise and coordination in show jumping: Investigating lumbar motion - Régnault, N.; Olivier, A.; Bideau, N. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
The objective of this study was to evaluate the influence of expertise on the coordination between the rider and their horse during the approach and reception phases in show jumping. Sixteen riders, divided into two groups (professionals, n=8; amateurs, n=8), performed a show jumping task while their movements were recorded using IMUs (XSens MVN) placed on them and on their horse`s sternum. The rider`s lumbar orientation (L3) and the horse`s sternum orientation were analysed to quantify coordination using continuous relative phase (CRP). Statistical analysis using Statistical Parametric Mapping (SPM) highlighted significant expertise-related differences at specific moments within the stride cycle. In professional riders, lumbar extension is weaker and their movement is in advance of the horse's movement suggesting enhanced anticipatory control.